Influence of High Amplitude Mould Vibration on the Morphology of Silicon in the Al-Si Alloy (A308) - Yadav S.; Kumar S.; Tewari S.P.; Ram S.C.; Prasad R.; Deo M.; Singh J.K. (My University, 2025)
Today’s casting industries strive to produce high-quality cast components in an efficient, cost-effective, eco-friendly, and sustainable way. To achieve this, with an indigenously developed, well-controlled digital vibratory setup, this study examines the effect of high amplitude vibration on the density, silicon morphology, and mechanical properties of A308 alloy. The metallurgical alterations were evaluated by optical microscopy, x-ray diffraction analysis, scanning electron microscopy, and energy dispersive spectroscopy. The size of α-Al grains, SDAS, length, width, and aspect ratio of eutectic Si particles decreased by 53%, 63%, 71%, 18%, and 62%, respectively. In comparison, the shape factor and density increased by 39% and 2.5%, respectively. Consequently, yield strength, ultimate tensile strength, % elongation, and microhardness increased by 16%, 25%, 17%, and 42%, respectively, at 2.5 mm amplitude and 10 Hz frequency compared with the conventional casting method. Refinement in eutectic silicon particle size (length, width and aspect ratio) and shape (plate to fibrous), dendrite fragmentation, structural uniformity, decreased porosities, and subsequent increase in density contributed to this improvement in mechanical properties. The SEM fractographs of tensile test samples showed a transgranular brittle fracture. At 10 Hz frequency, the fracture surfaces exhibit brittle fracture mode with partial ductility. © 2022, The Author(s), under exclusive licence to Springer Nature B.V.